ANALISIS PERAN ADMINISTRASI PEMBANGUNAN DALAM PENINGKATAN KAPASITAS SUMBER DAYA MANUSIA APARATUR SIPIL NEGARA DI ERA DIGITAL - Rohida, Leni; Nuraeni, Tia; Guritno, Ajeng Putri Wulan; Kasanah, Silviyatun (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The digital era demands that the Indonesian bureaucracy adapt through the implementation of an Electronic-Based Government System (ESG). The success of digital transformation is largely determined by the capabilities of the State Civil Apparatus (Civil Servants) as public administration implementers. However, limited digital literacy, intergenerational skill gaps, irrelevant training, a conservative organizational culture, and disparities in digital infrastructure are obstacles to realizing an effective digital bureaucracy. This study aims to analyze the role of development administration in increasing the capacity of civil servants (ASN) using the Grindle capacity building approach, which encompasses individual, organizational, and system development. The method used is qualitative-descriptive through literature studies and policy analysis related to the digital transformation of the bureaucracy and the development of civil servant human resources. The results of the study indicate that improving digital literacy, technical competence, and adaptive mindsets of civil servants is necessary at the individual level, while organizations require flexible, collaborative structures and visionary leadership. At the system level, regulatory support, policy integration, and the provision of digital infrastructure are needed. The results of this study demonstrate that development administration plays a strategic role in directing digital transformation through comprehensive capacity building of civil servants